Solve -6x-6y-2x=14 -6x+6y-4z=22 -5-y+3z=-7

Expert Answers info

sciencesolve eNotes educator | Certified Educator

calendarEducator since 2011

write5,349 answers

starTop subjects are Math, Science, and Business

You should eliminate one variable, hence, you need to add the first and the second equations to eliminate y such that:

`-6x - 6y - 2z - 6x + 6y - 4z = 14 + 22`

`-12x - 6z = 36`

Dividing by -6 yields:

`2x + z = -6`

You need to multiplicate the third equation by 6 such that:

`6(-5x-y+3z)=6*(-7) => -30x - 6y + 18z = -42`

You need to add the third...

(The entire section contains 208 words.)

Unlock This Answer Now


check Approved by eNotes Editorial